2017
DOI: 10.1021/acsphotonics.7b00501
|View full text |Cite
|
Sign up to set email alerts
|

Generating Optical Birefringence and Chirality in Silicon Nanowire Dimers

Abstract: Narrow high refractive index nanowires sustain weakly guided modes with significant mode volume outside of the nanowire. This modal spillover makes them interesting photonic materials for a multitude of applications. In this article we fabricate dimers of nanowires with lengths up to 1.4 μm, radii down to 55 nm, and edge-to-edge separation down to 60 nm through anisotropic etching from crystalline silicon (Si). We investigate how the properties of the weakly confined fundamental HE1,1 mode in Si nanowires are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Numerically, the NW waveguide modes have been vastly investigated [13][14][15][16][17]. The properties of the confined fields have also recently lead to some new prospects in spin angular momentum formation [18], and near chiral field manipulation [19,20]. Finally, semiconductor NW hybridization with metallic layers has recently shown effects such as circular dichroism [21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerically, the NW waveguide modes have been vastly investigated [13][14][15][16][17]. The properties of the confined fields have also recently lead to some new prospects in spin angular momentum formation [18], and near chiral field manipulation [19,20]. Finally, semiconductor NW hybridization with metallic layers has recently shown effects such as circular dichroism [21].…”
Section: Introductionmentioning
confidence: 99%
“…Structures under investigation are hexagonal Si NWs, that can be patterned on Si substrate, e.g., by means of conventional electron beam lithography [ 32 , 33 ]. In what follows, we use a commercial-grade simulator based on the 3D Finite Difference Time Domain (FDTD) method by Lumerical [ 34 ] to simulate complex electromagnetic fields in the Si NW array, and later extract C factor; more details are given in Section 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In [ 26 ] we investigated GaAs NW modes at ~800 nm, where we showed that for linearly polarized excitation, the near-field chirality cancels out and the additional symmetry breaking (e.g., the asymmetric layer of Au) must be introduced in order to have a C of prevalently one sign. In [ 32 ], NW dimers are used to induce the optical chirality and the hotspots of high C enhancement. Here, we show that under circularly polarized (CP) excitation, achiral NW structure can generate the enhanced chirality in the NW border vicinity, without the additional symmetry breaking which would complicate the processing of a perspective device.…”
Section: Introductionmentioning
confidence: 99%
“…The oligomer waveguide modes can be understood to arise due to the overlapping and interaction of monomer modes in the individual nanowires, somewhat analogous to the hybridization model for resonant excitations in nanoparticle oligomers [10]. To the best of our knowledge, the modal properties of nanowire oligomer waveguide modes have not been previously reported or their hybridization origin discussed, at least beyond recognizing coupled HE 11 modes leading to birefringence in nanowire dimers [11,12]. Here, we will show that InGaAs nanowire dimers and tetramers on a GaAs substrate (assuming bottom-up growth) emitting in the telecommunication C band wavelength range can, indeed, possess modes that exhibit improved modal confinement factor and modal reflectivities compared to the monomer modes from which they originate.…”
Section: Introductionmentioning
confidence: 95%